Dysphagia as the Predominant Symptom in Chronic Tonsillopharyngitis with Acute Exacerbation: A Case Report - Dzaka Ogan Amirudin Lutfi; Indera Istiadi; Deoni Daniswara (MEDICINUS, 2026)
Introduction: Chronic tonsillopharyngitis typically presents with sore throat, fever, and enlarged tonsil. However, dysphagia as the predominant symptom in chronic tonsillopharyngitis with acute exacerbation is rarely reported and can have a significant impact on a patient’s quality of life. Case: A 25-year-old male presented to the emergency department with a three-day history of odynophagia, dysphagia, fever, and voice changes. Oropharyngeal examination revealed enlarged, hyperemic tonsils with dilated crypts containing debris. Laboratory findings showed marked leukocytosis with neutrophil predominance, suggesting bacterial infection. Oropharyngeal swab culture identified Streptococcus pyogenes,which was sensitive to multiple antibiotics including ceftriaxone and penicillin. The patient was diagnosed with chronic tonsillopharyngitis with acute exacerbation and treated with intravenous ceftriaxone, dexamethasone, ranitidine, andsupportive dietary modifications. Clinical improvement was observed, and the patient was discharged with oral medications and scheduled outpatient follow-up. Tonsillectomy was discussed but was declined by the patients. Conclusion: Thiscase highlights dysphagia could be a potential primary symptom in acute exacerbation of chronic tonsillopharyngitis, underscoring the importance of comprehensive evaluation and culture-guided antimicrobial therapy. Early recognition andappropriate management are crucial to prevent complications, reduce symptom severity, and improve patient outcomes.